The Impact of Integrating Authentic Assessment in Developing Students' English Learning Outcomes: A Meta-Analysis - Putri Syeril; Nur Sehang Thamrin; Maf'ulah Maf'ulah; Konder Manurung (MASI Mandiri Edukasi, 2026)
Despite growing interest in authentic assessment as a learner-centered approach in English language teaching, empirical findings on its effectiveness in improving students’ English learning outcomes remain inconsistent across contexts and assessment types. The absence of synthesized evidence makes it challenging for educators and policymakers to draw firm conclusions about its overall impact. Therefore, this study aims to systematically examine the effect of authentic assessment on students’ English learning outcomes using a meta-analytic approach. This study employed a quantitative meta-analysis by synthesizing data from 25 empirical studies published between 2015 and 2025. The studies were retrieved from Google Scholar using the Publish or Perish application and selected based on predefined inclusion criteria. Effect sizes were calculated using Hedges’ g, and a Random Effects Model was applied to estimate the pooled effect size while accounting for between-study variability. The results reveal a statistically significant positive effect of authentic assessment on students’ English learning outcomes, with a pooled effect size of g = 1.203 (z = 5.54, p < .001). Substantial heterogeneity was observed, justifying the use of the random-effects model. Funnel plot analysis indicates no serious publication bias. Overall, the findings confirm that authentic assessment has a strong and meaningful influence on English learning outcomes and supports its integration into English language teaching practices.